2012
DOI: 10.1155/2012/538474
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Diabetes on Epigenetic Modifications Leading to Diseases in the Offspring

Abstract: Gestational diabetes, occurring during the hyperglycemic period of pregnancy in maternal life, is a pathologic state that increases the incidence of complications in both mother and fetus. Offspring thus exposed to an adverse fetal and early postnatal environment may manifest increased susceptibility to a number of chronic diseases later in life. Compelling evidence for the role of epigenetic transmission in these complications has come from comparison of siblings born before and after the development of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 38 publications
1
61
0
2
Order By: Relevance
“…In pregnancies complicated by GDM, the signaling of insulin is impaired so that glucose uptake or production cannot be stimulated or suppressed. Like in other forms of hyperglycemia, GDM affected maternal pancreatic β-cells do not function sufficiently to provide the physiological insulin requirement resulting in decreased insulin sensitivity (increased insulin resistance) coupled with an inadequate insulin response via impairment in the insulin signaling mechanism (2)(3)(4)(5)(6)(7)(8)(9). GDM is associated with placental pathology and various maternal and fetal complications during pregnancy, birth and later in life (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In pregnancies complicated by GDM, the signaling of insulin is impaired so that glucose uptake or production cannot be stimulated or suppressed. Like in other forms of hyperglycemia, GDM affected maternal pancreatic β-cells do not function sufficiently to provide the physiological insulin requirement resulting in decreased insulin sensitivity (increased insulin resistance) coupled with an inadequate insulin response via impairment in the insulin signaling mechanism (2)(3)(4)(5)(6)(7)(8)(9). GDM is associated with placental pathology and various maternal and fetal complications during pregnancy, birth and later in life (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Data suggest that exposure to a diabetogenic environment is associated with increased dyslipidemia (increased total LDL), subclinical vascular inflammation and endothelial dysfunction processes in the offspring, all of which are related to the development of cardiovascular diseases in the future [30]. Another fetal implication of exposure to GDM is the development of morphological abnormalities in Langerhans' islets in offspring, demonstrated through its abnormal form, as well as through hyperplasia and hypertrophy of the same [9].…”
Section: Impact Of Birth Weight On Metabolic and Cardiovascular Risksmentioning
confidence: 99%
“…These studies correlated the birth weight with the incidence of adult-onset diseases and proposed that the adverse fetal environment with nutritional deficiency followed by high nutritional intake during adulthood could be responsible for the development of chronic diseases in adulthood [30].…”
Section: Impact Of Birth Weight On Metabolic and Cardiovascular Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hyperglycemia during pregnancy could have a teratogenic effect by altering the embryonic epigenome, leading to defects like CAKUT in the fetus. 12,13 What are the implications of findings that link epigenetic changes to diabetic embryopathy? Other than CAKUT, neural tube defects in the fetus are associated with maternal diabetes, and recent studies have shown that the underlying mechanisms probably involve tissue-specific epigenetic changes and concomitant altered gene expression in neural stem cells.…”
mentioning
confidence: 99%